2020
DOI: 10.3390/biom10050696
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Functions, Energy Metabolism and Protein Glycosylation are Interconnected Processes Mediating Resistance to Bortezomib in Multiple Myeloma Cells

Abstract: The proteasome inhibitor bortezomib (BTZ) has emerged as an effective drug for the treatment of multiple myeloma even though many patients relapse from BTZ therapy. The present study investigated the metabolic pathways underlying the acquisition of bortezomib resistance in multiple myeloma. We used two different clones of multiple myeloma cell lines exhibiting different sensitivities to BTZ (U266 and U266-R) and compared them in terms of metabolic profile, mitochondrial fitness and redox balance homeostasis ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 66 publications
2
36
0
Order By: Relevance
“…ROS, adaptation to ROS, and mitochondrial biogenesis appear to form a self-amplifying feedback loop to sustain recurrence, as shown in CLL ( 119 ). However, in other settings, like MM, bioenergetics of tumor cells can change, as consequence of increased mitochondrial biomass and function, as part of the adaptive response to drug-induced stress ( 139 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS, adaptation to ROS, and mitochondrial biogenesis appear to form a self-amplifying feedback loop to sustain recurrence, as shown in CLL ( 119 ). However, in other settings, like MM, bioenergetics of tumor cells can change, as consequence of increased mitochondrial biomass and function, as part of the adaptive response to drug-induced stress ( 139 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bioenergetics changes, associated to increased mitochondrial biomass and function, can be elicited as part of the adaptive response to treatment (135)(136)(137)(138). In vitro, human MM cell lines resistant to bortezomib or dexamethasone have higher concentrations of ATP, NADH/NADPH ratio, associated to hyperpolarization of mitochondrial membrane leading to impaired drug response (137,139). In vitro, pre-treament with the OX-PHOS inhibitor tigecycline can increase bortezomib sensitivity (Alejandra Ortiz-Ruiz, ASH 2019, poster 4408) (140).…”
Section: Mitochondrial Fitness Mediates Resistance To Bortezomib In Mmentioning
confidence: 99%
“…To support this hypothesis, it is important to note that U266-R showed constitutively increased TLR4 expression and signalling, as well as higher values of mitochondrial mass. Additionally, we previously found that U266 cells resistant to BTZ had higher values of parameters reflecting mitochondrial function (membrane potential, ATP/ADP ratio, NAD + /NADH ratio) than those measured in U266 sensitive to drugs, thereby confirming that the PI-resistant phenotype is accompanied by an increase in mitochondrial biomass and increased reliance on mitochondrial respiration [26,28,40,41]. Thus, since TLR4 regulates mitochondrial biogenesis and BTZ-resistant cells rely on mitochondrial fitness, a link among TLR4 upregulation and PI resistance may exist.…”
Section: Discussionmentioning
confidence: 81%
“…Increased OXPHOS has been found in MM cells from both relapsed and drug resistant patients [27]. Recently, we characterized the biochemical, metabolic and molecular features of a U266 clone resistant to BTZ (U266-R), both under resting conditions and after BTZ exposure [23,28]. In comparison to the sensitive clone (U266-S), U266-R based their resistance to BTZ on changes of various genes and protein expressions, several of which are involved in mitochondrial dynamics and protein glycosylation.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular stress sensors and signaling organelles, mitochondria, are involved in cellular adaptation to the environment. A preclinical research indicated that increased expression of antioxidant enzymes (GSTK1) and higher concentrations of glycosylated UDP‐derivatives in the PI‐resistant MM cell line, to survive the cells by declining the counteraction of ROS‐mediated cell injury and preventing mitochondrial biogenesis inhibition 22 . Oxidative stress has been considered as an important factor of bortezomib cytotoxicity in myeloma and nonmyeloma cells.…”
Section: Mechanisms Of Drug Resistance Of Pismentioning
confidence: 99%